Estudo da produção de inulinase por fermentação em estado sólido utilizando como substrato o resíduo úmido cervejeiro e o melaço de cana-de-açúcar - Yupanqui Mendoza, Sergio Luis (2021)
The wet brewing residue (WBR) and sugarcane molasses are by-products of the beer and sugar industries, respectively, which have potential application in biotechnological processes, making them interesting alternatives for their use as substrates in fermentations, aiming produce compounds of industrial interest such as the synthesis of enzymes. In this context, this work aimed to produce Kluyveromyces marxianus ATCC 36907 inulinases using solid-state fermentation under optimized conditions. Initially, the chemical characterization of WBR and cane molasses was carried out, followed by the evaluation of three pre-treatment conditions for cane molasses (activated carbon, EDTA and sulfuric acid) in order to remove mineral compounds that are inhibitors of enzyme production. . The second stage consisted of a previous evaluation in solid- state fermentation of the molasses concentration, incubation time and humidity variables on the inulinase activity. For the optimization studies, a Plackett-Burman (PB) planning and the Central Rotational Composite Design were used. From the optimized results of inulinase activity, a kinetic evaluation of enzymatic production was performed under optimal conditions and the calculation of productivity, followed by a partial characterization of the enzyme produced. The results of the characterization for WBR and cane molasses, showed that both substrates present an important source of proteins and carbohydrates, respectively. The use of a sulfuric acid treatment for sugarcane molasses was defined as the most appropriate to favor increased enzyme activity. Preliminary analyzes of solid-state fermentation determined that the highest enzyme activity was obtained in 72 h and moisture in the medium in 75%. The evaluation of significant variables through PB planning determined that only three variables (temperature of incubation, concentration of cane molasses and yeast extract) showed positive statistical significance. Through the optimization analysis, it was possible to obtain a maximum inulinase activity at 239,38 U/g and productivity of 3,69 U/g.h, using the values optimized for incubation temperature at 37,5 °C, molasses concentration of 47,1% w/w and 0,16 g of yeast extract for every 5 g of brewing residue. Finally, regarding the characterization, the enzyme showed good stability between 50 and 55 °C and a wide pH range between 4,0 and 6,0, maintaining more than 80% of its activity until 22h of incubation. The kinetic constants corresponding to the apparent Km and Vmax were 13,6 mM and 3,69 g/L.min, respectively. According to the data obtained, it appears that the enzyme obtained in the experiment showed high enzymatic activity, good productivity and stability under different pH and temperature conditions. In this way, the study demonstrates the importance of using agro-industrial residues such as RUC and sugarcane molasses, to be considered candidate substrates in the formulation of solid culture media for the synthesis of enzymes of industrial interest.